2012
DOI: 10.4067/s0718-19572012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la temperatura y salinidad del agua en la incubación de huevos de botete diana Sphoeroides annulatus

Abstract: Abstract.-The effects of different water temperatures (22, 25, 28 and 31ºC) and salinities between 0 and 60 psu (with intervals of 5 psu) on egg incubation of the bullseye puffer (Sphoeroides annulatus) were evaluated in this study. The embryos could not develop at 22ºC and the highest hatching rate for normal larvae was observed at 28ºC. At 0, 50, 55 and 60 psu larvae were unable to develop. Highest hatching rates were obtained at 25, 30 and 35 psu. It was concluded that water temperature and salinity affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…This study showed that S. annulatus embryos do not have the capacity to develop normally in 5 ups, the majority of the organisms exposed to these conditions (97.4%) did not hatch and those who hatched (2.6%) died within the next 3 h. Similar results were obtained by Abdo‐de la Parra et al . (), corroborating this response.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This study showed that S. annulatus embryos do not have the capacity to develop normally in 5 ups, the majority of the organisms exposed to these conditions (97.4%) did not hatch and those who hatched (2.6%) died within the next 3 h. Similar results were obtained by Abdo‐de la Parra et al . (), corroborating this response.…”
Section: Discussionsupporting
confidence: 77%
“…The selected female had oocytes ~0.5 mm in diameter of size (according to Abdo‐de la Parra et al . ). Implant analogue of 200 mg luteinizing hormone (LHRHa; Des‐Gly10 [D‐Ala6]‐Luteinizing hormone‐releasing hormone ethylamide) EVAc type, was applied into a female, to induce maturation and ovulation of the gametes.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Los antecedentes señalan que la temperatura controla el tiempo de incubación de los huevos y la supervivencia de embriones y larvas; cuando los huevos son incubados fuera de un intervalo óptimo, el desarrollo embrionario puede acelerarse o retardarse, produciendo embriones y larvas deformes, bajos porcentajes de eclosión y elevada mortalidad de larvas eclosionadas (Abdo-de la Parra et al, 2012). Si bien no hay información acerca de las condiciones óptimas para el desarrollo embrionario de Sarda ch.…”
Section: Resumen Del Modelounclassified